Morphologically differentiated sex chromosomes in neotropical freshwater fish - Toledo, L. F. de Almeida; Foresti, F. (Springer Nature, 2001)
A general survey of the occurrence of morphologically differentiated sex chromosomes in the neotropical freshwater fishes is presented. The total number of 32 occurrences involving simple XX-XY and ZZ-ZW, and multiple X1X2Y, XY1Y2 and ZW1W2 sex chromosome systems is described, with comments on the aspects of sex chromosome evolution in this fish fauna. The occurrence of different sex chromosome systems in related species of the same genus, or in different populations of the same nominal species, involving male and sometimes female heterogamety, and differences in the molecular composition of sex-linked heterochromatin, are considered as indicative of the early stage of sex chromosomes evolution in fish.
Keywords: Fish cytogenetics; Neotropical fishes; Sex-chromosomes; XX-XY; ZZ-ZW; Pisces; fresh water; animal; female; fish; genetics; karyotyping; male; sex chromosome; species difference; Animals; Female; Fishes; Fresh Water; Karyotyping; Male; Sex Chromosomes; Species Specificity